Online Store Marketing Strategy and Its Implications on Consumptive Behavior in Fashion Products of IAIN Kediri Students: Islamic Marketing and Islamic Consumption Perspective - Fatmawatie, Naning (Fakultas Ekonomi, UIN Maliki Malang, 2020)
The online store marketing strategy has made people's lifestyles change to become more modern. This is influenced by culture, mindset, needs and the desire to change. In online store marketing, the distance between sellers and buyers has been very close and transactions can be done easily. This study aims to analyze the implementation of marketing strategies in online stores in Indonesia, analyze the consumptive behavior of IAIN Kediri student fashion products, analyze the practice of marketing strategies to online stores in Indonesia in terms of Islamic marketing and to analyze consumptive behavior in IAIN Kediri student fashion products in terms of consumption of Islam. This research is a descriptive study using a qualitative approach, with a purposive technique as an information determination technique. The result indicates that the online store marketing strategy in Indonesia applies a marketplace, low prices, free shipping and bonus services. The study shows that students of IAIN Kediri spend more through Lazada's online store, on favorite fashion products. The frequency of shopping for fashion products at online stores is at one most once a month and more than one month. The implementation of marketing strategies for online stores must be based on the theistic (rabbaniyyah), ethical (akhlaqiyyah), realistic (al-waqiyyah) and humanistic (insaniyyah) principles.